Rethinking ancient Maya social organization : replacing "lineage" with "house". - Gillespie, Susan D. (American Antropological Association, 2000)
Long-standing disagreements concerning prehispanic Maya kinship and social organization have focused on the nature of their corporate groups, generally presumed to have been lineages. Specific debates center on whether the lineages were patrilineal or incorporated some kind of double-descent reckoning, how descent was combined with locality to define a group, and the status of lineage-outsiders within a group. It is argued here that Maya social organization is better approached within the contemporary critique of kinship, replacing "lineage" with Lévi-Strauss's model of the "house"—a corporate group maintaining an estate perpetuated by the recruitment of members whose relationships are expressed "in the language" of kinship and affinity and affirmed by purposeful actions. In this perspective, the operation of corporate groups is the primary concern, and relationships construed in terms of consanguinity and affinity are seen as strategies pursued to enhance and perpetuate the group, [ancestor veneration, house society, kinship, Maya, social organization]